A novel metformin derivative showed improvement of lipid metabolism in obese rats with type 2 diabetes. (13th April 2020) - Chen, Deqi; Jia, Dan; Wu, Xia; Shi, Kexin; Ren, Cui; Dou, Yonghui; Guo, Mingxin; Wang, Juanxia; Ma, Min; Wu, Zhengzhi; Shi, He‐Yong; Li, Weimin; et al.
Abstract: In this study, we investigated the lipid metabolism regulatory activity of a novel metformin derivative (MD568) and its potential mechanism of action in obese rats with type 2 diabetes mellitus (T2 DM). Previous gene chip analysis of 3T3‐L1 cells have shown that MD568 regulates the transcription of genes involved in the peroxisome proliferator‐activated receptor (PPAR) signalling pathway, fatty acid metabolism, and glycerolipid metabolism. In this study, obese T2 DM rats were treated with MD568 (200 mg/kg) for 8 weeks. Results showed that MD568 significantly reduced the body weight gain, plasma glucose, insulin, total cholesterol, triglyceride, and low‐density lipoprotein cholesterol levels. MD568 treatment also improved the insulin resistance of obese T2 DM model rats. In particular, in white adipose tissue, MD568 inhibited the excessive volume increment of adipose cells by down‐regulating the protein levels of CCAAT/enhancer‐binding protein‐α (C/EBP‐α) and PPAR‐γ, as well as the transcription of their target lipid metabolism‐related genes. In the liver, MD568 inhibited hepatic fatty lesions and interfered with hepatic gluconeogenesis by regulating the expression of lipid metabolism‐related genes and glycogen‐related kinases. In conclusion, our results suggest that the newly synthesized MD568 affects the maintenance of lipid homeostasis in obese type 2 diabetic rats.